2022
DOI: 10.3389/fcimb.2022.922996
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of leptospirosis complicated by pulmonary tuberculosis complemented by metagenomic next-generation sequencing: A case report

Abstract: Leptospirosis is a zoonotic infection caused by the pathogenic Leptospira. Leptospirosis is transmitted mainly through contact with contaminated rivers, lakes, or animals carrying Leptospira. Human leptospirosis has a wide range of non-specific clinical manifestations ranging from fever, hypotension, and myalgia to multi-organ dysfunction, which severely hampers the timely clinical diagnosis and treatment of leptospirosis. Therefore, there is an urgent clinical need for an efficient strategy/method that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…mNGS can quickly identify multiple pathogens with unbiased, wide coverage, high e ciency, as well as assumption and minimize missed diagnosis [2,3] . There have been many reports of Mycobacterium tuberculosis infection being diagnosed through mNGS [15,16] . In addition, the retrospective study showed that the sensitivity of mNGS in tuberculosis diagnosis was 46%, signi cantly higher than that of the culture method [17] .…”
Section: Discussionmentioning
confidence: 99%
“…mNGS can quickly identify multiple pathogens with unbiased, wide coverage, high e ciency, as well as assumption and minimize missed diagnosis [2,3] . There have been many reports of Mycobacterium tuberculosis infection being diagnosed through mNGS [15,16] . In addition, the retrospective study showed that the sensitivity of mNGS in tuberculosis diagnosis was 46%, signi cantly higher than that of the culture method [17] .…”
Section: Discussionmentioning
confidence: 99%
“…These disasters increase the risk of water sources and the environment becoming contaminated with Leptospira bacteria. Secondly, poor sanitation and hygiene practices, especially in urban areas, contribute to the spread of the disease 16 . Additionally, there is a lack of awareness and understanding about leptospirosis among the general population, health workers, and policymakers, which hampers effective prevention and control efforts.…”
Section: Introductionmentioning
confidence: 99%